Variations of wheat (Triticum aestivum L.) chromosomes caused by the 5A chromosomes with complex cytological structure - Zou, Yang; Luo, Jie; Tang, Zongxiang; Fu, Shulan (Frontiers in Plant Science, 2022)
To study the effects of structural alterations of chromosomes caused by tandem repeats on the meiotic recombination, the wheat (Triticum aestivum L.) 5A chromosomes with different structure from ten wheat cultivars were used to investigate their meiotic recombination using non-denaturing fluorescence in situ hybridization (ND-FISH) technology. Fifteen cross combinations were carried out and they were divided into seven F1 categories. The structural difference between the intercalary regions of the long arms of the two 5A chromosomes (5AL) in the F1 categories III, VI and VII was greater than that in the categories I and II, subsequently, the recombination frequencies in the distal regions of the 5AL arm in the progenies from the three categories were significantly lower than that from the categories I and II. For the two 5A chromosomes in the F1 categories VI and VII, the structural differences in the distal regions of both of the two arms were greater than that in the categories IV and V. So, the recombination frequencies in the intercalary region of the 5AL arm in the progeny from the categories IV and V were higher than that in the progeny from the categories VI and VII. The breakage of 5A chromosome together with the 5A translocations and the breakage of some other chromosomes were observed in the progeny from the F1 categories V, VI and VII. These chromosomal variations were not observed in the progenies from the other four F1 categories. In conclusion, the smaller structural difference between the 5A chromosomes in distal regions of the two arms resulted in a higher recombination frequency in interstitial region and vice versa. The the 5A chromosome with complex cytological structure can be used to induce genetic variations of wheat genome.